resolva a equação
[tex] \frac{3x + 1}{2} = - 16[/tex]​


Resposta :

Resposta:

[tex]\frac{3x + 1}{2} = -16[/tex]

Podemos fazer a operação inversa:

-16 . 2 = 3x + 1

  -32 = 3x + 1

  -32 - 1 = 3x

      -33 = 3x

       x = -33/3

       x = -11

Explicação passo-a-passo:

espero ter ajudado e oi novamente!

Explicação passo-a-passo:

[tex] \dfrac{3x + 1}{2} = - 16[/tex]

[tex]3x + 1 = - 32[/tex]

[tex]3x = - 32 - 1[/tex]

[tex]3x = - 33[/tex]

[tex]x = - \dfrac{33}{3} [/tex]

[tex]x = > - 11[/tex]